How to wed a warrior ebook - English, Christy (Broadswords and Ballrooms, 2016)
He's the scourge of the Season... Reasons to quit London: 1. It's not the Highlands. 2. It will never be the Highlands. 3. It's full of the bloody English. When his wild spitfire of a sister makes a scene by drawing a claymore in Hyde Park, Highlander Robert Waters knows something must be done. To forestall the inevitable scandal, he hires widowed Prudence Whittaker to teach his sister how to be a lady—never expecting to find unbridled passion beneath the clever Englishwoman's prim exterior. Mrs. Whittaker is a fraud. Born Lady Prudence Farthington, daughter of the ruined earl of Lynwood, she's never even been married. In order to make her way in the world, she has to rely on her wits and a web of lies...lies a sexy Highlander is all too close to unraveling. He swears he will possess her; she vows he will do nothing of the sort. Yet as passions heat, Prudence comes to realize the illicit pleasure that can be had in going toe-to-toe with a Scot. Broadswords and Ballrooms: How to Seduce a Scot How to Wed a Warrior How to Train Your Highlander Praise for Christy English: "Grace Burrowes and Amanda Quick fans will enjoy the strong ladies in the latest fun read from the ascending English." —Booklist "With its quick and engaging characters, here's a pleasurable evening's escape." —RT Book Reviews